The Doba of Ethiopia In the 15th and 16th Centuries - Mesfin Tadesse Belay; Mengiste Zewdu Tessema; Wubie Tadege Yenehun (Cogent Arts & Humanities)
This review article is a historical narrative of the Doba people, who inhabited the Northeast Amhara region and Southern Tigray in what is now referred to as Raya, Ethiopia. The timeframe under consideration spans from ancient times until their eventual assimilation into the local communities. Despite the challenge of scant direct memory among the current residents of Raya, the historical traces of the Doba people are discovered through diverse sources such as chronicles, accounts from travelers, and church documents, either presented in translation or referenced within secondary materials. The article seeks to illuminate various aspects of the Doba people’s existence during the 15th and 16th centuries. This includes exploring their way of life, the geographical context of Raya, and the fluid nature of the Doba identity as it transformed interactions with other communities.